The Effectiveness of Teaching English of EYL Course In Elementary School - Aprilia Ningsih; Dian Susyla; Ria Angraini; Waslurachim Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to describe the effectiveness of teaching English of EYL Course in SDN 07 Kota Bengkulu. It was designed as a qualitative research in which the data were obtained via interview and documentation. The data were also analyzed by applying main indicators and criteria in measuring teaching effectiveness. On the one hand, the indicators were consisted of mastery learning, student learning activity, management ability, and student responses. On the other hand, the criteria comprised time allocation and student motivation. The results indicated that the apprentice teacher of Muhammadiyah University of Bengkulu mastered in delivering lesson materials. Then, the students showed the different attitudes during attending the class of EYL. Some of whom were active and some tended to be passive. However, management skill of the apprentice teacher was not called to be well-structured yet. It was also observed from their ability to allocate time in delivering lesson materials of EYL. Additionally, motivation of the students mostly came from their perspective about English. Most of whom considered having skill in speaking English was very cool. In conclusion, teaching EYL in SDN 07 Kota Bengkulu is effective to conduct because both indicators and criteria have tendency to be positive, even though ability of the apprentice teachers are still not professional yet.Key Words: Effectiveness, EYL Course, Elementary School.